Technology-Based Interactive Mathematics Learning: A Case Study of Community Service Activities at SMA PGRI Cicalengka - Syarifudin, Abdul Gazir; Amelia, Rika; Hidayana, Rizki Apriva; Megantara, Tubagus Robbi; Kholipah, Nenden Siti Nur (International Journal of Research in Community Services, 2025)
The This community service activity was conducted through collaboration between the Mathematics Study Program of the Republic of Indonesia National University and SMA PGRI Cicalengka, involving 80 participants consisting of 12th-grade students. The one-day program aimed to enhance students' understanding of mathematics applications in science and technology (IPTEK), including programming algorithm simulations, through interactive lectures. The sessions focused on developing logical thinking, strategic problem-solving skills, and awareness of mathematics' role in daily life. The event began with an opening ceremony attended by school representatives, faculty members, and university officials. Two main sessions were delivered: the first covered practical applications of mathematics in everyday contexts, while the second highlighted its role in advancing IPTEK through online gaming. Active participation was observed during Q&A sessions. The program concluded with a satisfaction survey, with results analyzed and published as part of the activity's outcomes. Overall, this initiative successfully introduced students to the interdisciplinary relevance of mathematics while fostering engagement through interactive learning. Follow-up evaluations will assess its impact on strengthening students' appreciation of mathematics in technological and real-world applications.